2010
DOI: 10.3171/2010.1.focus1011
|View full text |Cite
|
Sign up to set email alerts
|

Resident learning curve for minimal-access transforaminal lumbar interbody fusion in a military training program

Abstract: Object Minimal-access transforaminal lumbar interbody fusion (TLIF) has gained popularity as a method of achieving interbody fusion via a posterior-only approach with the aim of minimizing injury to adjacent tissue. While many studies have reported successful outcomes, questions remain regarding the potential learning curve for successfully completing this procedure. The goal of this study, based on a single resident's experience at the only Accreditation Council for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…10 Our data complete this information with regard to discectomy and endplate preparation. 10 Our data complete this information with regard to discectomy and endplate preparation.…”
Section: Discussionmentioning
confidence: 70%
“…10 Our data complete this information with regard to discectomy and endplate preparation. 10 Our data complete this information with regard to discectomy and endplate preparation.…”
Section: Discussionmentioning
confidence: 70%
“…investigated 28 minimal access transforaminal lumbar interbody fusion procedures done by a single resident, and suggested that this procedure can be safely performed in a training environment. 29 However, these studies are limited by their small sample size and their narrow focus on relatively specialized procedures. Given the paucity and focused aspects of previous investigations, the goal of our study was to capture a broader range of neurosurgical cases for a more robust and generalized analysis of resident involvement in the neurosurgical setting.…”
Section: Discussion Study Rationalementioning
confidence: 99%
“…There are limited data to suggest that approximately 15-30 cases are required to meet a standard level of individual proficiency for a particular procedure, 16 and the minimum requirements set out by the ACGME are reflective of this. The manner in which the UF VA-DoD program exceeds these minimums highlights the clear benefit of having this civilian partnership, which will result in well-trained neurosurgeons who are fully prepared for the battlefield.…”
Section: Nontrauma Casesmentioning
confidence: 99%